Shopping for Health: Beans, Peas, and Lentils - Lakshmi Mahan; Lauren Foster; Wendy Dahl (EDIS, 2011)
Beans are one of the most wholesome foods in nature. They come packed with protein, fiber, and vitamins. Naturally low in fat, they contain no cholesterol and are very low in saturated fat. Some are also high in antioxidants. This 4-page fact sheet provides nutritional information and recipes. Written by Lakshmi Mahan, Lauren Foster, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, June 2011. Minor revisions January 2014, May 2016, and August 2019.